Facile Fabrication of Silk Fibroin/Off-Stoichiometry Thiol-Ene (OSTE) Microneedle Array Patches - Yuqian Yang; Zhiqing Xiao; Lexin Sun; Zitao Feng; Zejingqiu Chen; Weijin Guo (Micromachines, 2023)
Microneedles have been used in various applications in biomedical engineering, including drug delivery, biosensing, and vaccine delivery. In this study, we develop a novel protocol to fabricate silk fibroin/off-stoichiometry thiol-ene (OSTE) hybrid microneedle array patches. Silk fibroin, as a natural biomaterial, has been proven to be suitable as a drug carrier. Firstly, drug (we use insulin in this experiment) dissolved in silk fibroin solution is deposited on a microneedle mold and dried thoroughly. After that, silk fibroin needle tips are formed on the OSTE base by replica molding. We investigated the influence of the silk fibroin concentration on the length of silk needle tips and found that the silk concentration had a small influence on the tip length. We also tested the mechanical strength of the microneedles by inserting them into gelatin gel for dummy drug delivery tests. Such composite structures have the potential to increase the delivery efficiency by delivering the whole silk tip into the dermis.